2017
DOI: 10.1371/journal.pone.0172568
|View full text |Cite
|
Sign up to set email alerts
|

Lung cancer specialist physicians’ attitudes towards e-cigarettes: A nationwide survey

Abstract: ObjectivesDespite a sharp increase in e-cigarette use, there is debate about whether e-cigarettes are a viable alternative for harm reduction, and the forms that regulation should take. Healthcare providers can be effective in offering guidance to patients and their families and shaping regulatory policy. We described lung cancer specialists’ attitudes toward e-cigarettes and its regulation.MethodsWe undertook a nationwide survey of pulmonologists, thoracic surgeons, medical and radiological oncologists who ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
53
2
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 23 publications
(71 citation statements)
references
References 23 publications
4
53
2
10
Order By: Relevance
“…Our findings also showed that just over half of the reported discussions about NVPs were initiated by the smokers themselves, and not by the HP, which may indicate that HPs do not feel entirely comfortable or confident bringing up the topic. This has also been found in other studies, where reasons for not advising about NVPs have included the HP's perceived uncertainty about the safety and efficacy of NVPs , negative beliefs , lack of knowledge , and lack of confidence in their own capacity to counsel smokers about NVPs . These cited studies, however, have mainly been conducted in the United States using convenience samples, with limited data on common practices in other countries.…”
Section: Discussionmentioning
confidence: 66%
See 2 more Smart Citations
“…Our findings also showed that just over half of the reported discussions about NVPs were initiated by the smokers themselves, and not by the HP, which may indicate that HPs do not feel entirely comfortable or confident bringing up the topic. This has also been found in other studies, where reasons for not advising about NVPs have included the HP's perceived uncertainty about the safety and efficacy of NVPs , negative beliefs , lack of knowledge , and lack of confidence in their own capacity to counsel smokers about NVPs . These cited studies, however, have mainly been conducted in the United States using convenience samples, with limited data on common practices in other countries.…”
Section: Discussionmentioning
confidence: 66%
“…Our findings showed that, overall, fewer than 10% of smokers reported having a discussion about NVPs with an HP in the last year. Moreover, a number of studies have shown that HPs are divided about recommending NVPs for smoking cessation . The results herein have shown that HPs rarely recommended NVPs to smokers (only 2% of smokers were encouraged to use an NVP, which was approximately a third among those who had a conversation about the topic).…”
Section: Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…However, British public health organizations have taken a more encouraging stance on ECIGS as a harm reduction innovation that should be promoted for smoking cessation; consequently, the majority of British practitioners ask patients about ECIG use . Given the more conservative approach in the USA, it is possible that oncology providers fear that discussing ECIGS may implicitly encourage use of ECIGS …”
Section: Discussionmentioning
confidence: 79%
“…31 Given the more conservative approach in the USA, it is possible that oncology providers fear that discussing ECIGS may implicitly encourage use of ECIGS. 32 Because smoking can cause adverse cancer outcomes, it is critical for oncologists to assist their patients with smoking cessation and to educate patients about the risks and benefits of using ECIGS. Consistent with our participants' perceptions, a recent report from the National Academies of Sciences, Engineering, and Medicine concluded that ECIGS are far less harmful than cigarettes.…”
Section: Discussionmentioning
confidence: 99%